Leadership Paradigms for Remote Agile Development How To Lead Your Team Remotely - Jakobus, Benjamin; Sena, Pedro Henrique Lobato; Souza, Claudio (Berkeley, CA : Apress : Imprint: Apress, 2022)
If you are asking yourself Why are my engineers unable to deliver?, Why are so many engineers leaving? or Why is our software riddled with bugs?, then you've come to the right place. This book acts as a concise, practical guide on how to lead successful agile projects in a remote environment. The authors draw from industry experience and a wide range of fields and disciplines--from software engineering to criminology and sociology--to teach you how to maintain technical oversight, manage deadlines, and calibrate expectations, while also creating and maintaining a healthy remote work environment. You will gain both practical tips grounded in reality, while learning why such tips work by navigating the background on which they are founded--from Broken Window Theory, Labeling Theory to the Dunning-Kruger Effect. Leadership Paradigms for Remote Agile Development will show you how to avoid the most common mistakes and pitfalls that cause engineering projects to fail while at the same time maintaining high ethical standards. You will: Manage feedback, reduce bureaucracy, create and adapt processes Understand what to look for in new hires Carve out a solid road to success for any type of software project.
Chapter 1 - Introduction -- Chapter 2 - Leadership -- Chapter 3 - Management- Chapter 4 - Hiring -- Chapter 5 - Quality -- Chapter 6 - Feedback -- Chapter 7 - Managing expectations -- Chapter 8 - Bureaucracy -- Chapter 9: Ethics -- Chapter 10 - Remote Work -- Afterword.
Keywords: Information technology-Management.; Business information services; Management; Personnel management; Entrepreneurship; New business enterprises; Business Process Management; IT in Business; Management; Human Resource Management; Entrepreneurship